2006
DOI: 10.4049/jimmunol.177.6.3782
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Susceptibility of Recombinant Polyclonal Antibodies to Inhibitory Anti-Variable Domain Antibody Responses

Abstract: The immunogenicity of therapeutic Abs is a concern as anti-drug Abs may impact negatively on the pharmacodynamics and safety profile of Ab drugs. The factors governing induction of anti-drug Abs are not fully understood. In this study, we describe a model based on mouse-human chimeric Abs for the study of Ab immunogenicity in vivo. Six chimeric Abs containing human V regions and mouse C regions were generated from six human anti-Rhesus D Abs and the Ag-binding characteristics of the parental human Abs were ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…In contrast, previous studies using interferon a2b transgenic mice showed that tolerance could be broken in response to administration of aggregated protein. 21 Important differences between the current study and the previous studies may be related to the natural function and abundance of the respective proteins, 5 as well as the mouse strains 60 used to generate the transgenic mice. The current study used the strain B6.SJL-Tg(HBB-GH1)420King/J, which results from the cross breeding of C57BL/6J with SJL strains, whereas the interferon a2b study was based on the strain FVB/N.…”
Section: Activated Dendritic Cells Can In Turn Activate T Cells Into mentioning
confidence: 93%
“…In contrast, previous studies using interferon a2b transgenic mice showed that tolerance could be broken in response to administration of aggregated protein. 21 Important differences between the current study and the previous studies may be related to the natural function and abundance of the respective proteins, 5 as well as the mouse strains 60 used to generate the transgenic mice. The current study used the strain B6.SJL-Tg(HBB-GH1)420King/J, which results from the cross breeding of C57BL/6J with SJL strains, whereas the interferon a2b study was based on the strain FVB/N.…”
Section: Activated Dendritic Cells Can In Turn Activate T Cells Into mentioning
confidence: 93%
“…Although the use of the respective animal proteins might help elucidate basic immunological properties of the molecules studied, animal and human MHC are not equivalent because they can have different amino acid side-chain restrictions. This is best illustrated by the variability of immune response to chimeric antibodies in different strains of inbred mice [38]. For human homologs, standard animal models are even less predictive because the induction of immunogenicity in humans is based on breaking B and T cell tolerance, although such models do allow comparison of relative immunogenicity of different preparations of the same protein.…”
Section: Animal Studiesmentioning
confidence: 99%
“…Plasmablast cells were isolated by flow cytometry and sorted into single wells of 96-well plates (50 plates per donor), and the antibody-containing supernatants were screened by a custom Luminex assay for PTx reactivity (see Table S1 in the supplemental material). The antibody variable heavy chain (V H ) and variable light chain (V L ) sequences were then amplified from PTx-reactive wells by use of established methodologies ( 14 , 15 ), resulting in identification of five unique antibody sequences ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%